2001
DOI: 10.1097/00001756-200107200-00043
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis-processing regions in the human parieto-occipital cortex

Abstract: We performed fMRI on the human parieto-occipital cortex in order to identify the neural processing regions of stereopsis. Visual stimulation for stereopsis was performed with a random-dot stereogram displayed in the image guides of a new binocular visual stimulation device that we developed. Interestingly, regions from the dorsal portion of the occipital lobe to the superior parietal lobule were activated by binocular disparity, while the inferior parietal lobule was not activated. Moreover, these regions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 21 publications
6
56
1
Order By: Relevance
“…However, later studies which performed analysis over a larger number of visual areas found that the activation levels are highest in dorsal occipito-parietal areas, such as V3A, V7, V4d-topo and caudal intraparietal sulcus relative to others [3,[5][6][7][8]. Moreover, considering all these studies together, the most consistent sites of activation for depth across many previous fMRI studies were V3A, V7, V4d-topo, or other lateral occipital areas, such as MT+, lateral occipital complex, and kinetic occipital area [2,3,5,6,8,10,13], as well as intraparietal sulcus [2,3,[6][7][8][9][10][11][12] and superior parietal lobe [2,6,7,8,[10][11][12]. In addition, ventral temporal cortical areas, including the fusiform gyrus, have also been noted to be depth selective [2,16,17].…”
Section: Binocular Depthmentioning
confidence: 70%
See 4 more Smart Citations
“…However, later studies which performed analysis over a larger number of visual areas found that the activation levels are highest in dorsal occipito-parietal areas, such as V3A, V7, V4d-topo and caudal intraparietal sulcus relative to others [3,[5][6][7][8]. Moreover, considering all these studies together, the most consistent sites of activation for depth across many previous fMRI studies were V3A, V7, V4d-topo, or other lateral occipital areas, such as MT+, lateral occipital complex, and kinetic occipital area [2,3,5,6,8,10,13], as well as intraparietal sulcus [2,3,[6][7][8][9][10][11][12] and superior parietal lobe [2,6,7,8,[10][11][12]. In addition, ventral temporal cortical areas, including the fusiform gyrus, have also been noted to be depth selective [2,16,17].…”
Section: Binocular Depthmentioning
confidence: 70%
“…In these studies, stimulus blocks showing images with depth were contrasted with blocks with no depth [2,3,6,7,[9][10][11][12]17], or correlated disparity versus anticorrelated disparity images [13]. Other depth studies used methods more similar to those used for binocular rivalry, such as multivoxel pattern analysis [8], event-related adaptation [15], event-related designs in which brain activation was correlated to changes in perceived depth [5,16], or adaptation in a block design to assess population responsiveness to different types of depth stimuli [14].…”
Section: Methodological Issues In Fmri Studies and Role Of Frontal Areasmentioning
confidence: 99%
See 3 more Smart Citations